أدب القضية الفلسطينية عند الشاعر السوري عمر أبو ريشة (دراسة تحليلية): The literature of the Palestinian cause according to the Syrian poet Omar Abu Risha (an analytical study) - الدكتور غسان بن صالح عبد المجيد, (Al Manhal Research Journal, 2024)
This study deals with an aspect of the writer's commitment to the concerns of the people and their suffering and the scourge that the Zionist occupation dragged on the Arab and Islamic peoples in general, and on the struggling Palestinian people in particular, as the shovels of global Zionism since the beginning of the twentieth century began to destroy the edifice of Palestine and tamper with it, and the features of this danger were not clear to many Arab intellectuals, as the level of awareness of the schemes of global Zionism is low, as well as the interruption of communication between members of the Arab world east and west, but the signs of sensing The danger was evident in the appeals of Syrian poets, especially those who saw smoke and realized that the fire had broken out. We must monitor the positions of Syrian poets on the question of Palestine, and display their portrayal of the conditions of Palestinian refugees, and expose them to deceive the Zionists and the West behind them, and condemn poets of their crimes, and feel their optimism for victory and return to Palestine.